2021
DOI: 10.1016/j.omtn.2021.06.002
|View full text |Cite
|
Sign up to set email alerts
|

EFNA4 promotes cell proliferation and tumor metastasis in hepatocellular carcinoma through a PIK3R2/GSK3β/β-catenin positive feedback loop

Abstract: Rapid tumor progression, metastasis, and diagnosis in advanced stages of disease are the main reasons for the short survival time and high mortality rate of patients with hepatocellular carcinoma (HCC). Ephrin A4 (EFNA4), the ligand of the EPH family, participates in the development of blood vessels and epithelium by regulating cell migration and rejection. In our study, based on bioinformatics analyses, we found that EFNA4 was highly expressed and led to poor prognosis in patients with HCC. We demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 28 publications
2
27
0
Order By: Relevance
“…EFNA3 helps in proliferation, invasion of peripheral nerve sheath tumors, and tumor angiogenesis [ 44 , 45 ]. EFNA4 potentially promotes hepatocellular carcinoma invasion and migration via the GSK3β signaling pathway [ 15 ], and is involved in the invasion of glioma via Akt signaling [ 46 ]. Furthermore, EFNA5 promotes the malignant progression of pancreatic cancer [ 47 ] but played a tumor suppressor role in glioma by inhibiting EGFR [ 48 ], tumor invasiveness, and metastasis in hepatoma and colorectal cancer [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…EFNA3 helps in proliferation, invasion of peripheral nerve sheath tumors, and tumor angiogenesis [ 44 , 45 ]. EFNA4 potentially promotes hepatocellular carcinoma invasion and migration via the GSK3β signaling pathway [ 15 ], and is involved in the invasion of glioma via Akt signaling [ 46 ]. Furthermore, EFNA5 promotes the malignant progression of pancreatic cancer [ 47 ] but played a tumor suppressor role in glioma by inhibiting EGFR [ 48 ], tumor invasiveness, and metastasis in hepatoma and colorectal cancer [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…EFNA1 overexpression is linked to low DFS of hepatoma [ 70 ]. EFNA4 expression is linked to poor prognosis in hepatoma [ 15 ]. High EFNA5 expression is associated with lower OS in ovarian carcinoma [ 71 ] and pancreatic cancer [ 47 ] but associated with a better prognosis in prostate cancer [ 17 ], hepatoma [ 49 ], and glioblastoma [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EFNA4 is up-regulated in hepatocellular carcinoma correlating to a poor prognosis. Its overexpression mainly affects the PIK3R2/GSK3β/β -catenin pathway which significantly promotes the progression (proliferation and migration) of hepatocellular carcinoma ( Lin et al, 2021 ). In recent years, there has also been reports on EphA1 and EphA2 in the field of gastric cancer ( Rudno-Rudzińska et al, 2017 ; Peng C et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that members of ephrin family play an important role in the pattern of nervous system, vascular system assembly and angiogenesis [20][21][22][23][24]. EFNA4 has also been reported to be involved in the proliferation of oral squamous cell carcinoma, hepatocellular carcinoma and gastric cancer [25][26][27]. However, the functions and mechanisms of EFNA4 in lung cancer are still not clear.…”
Section: Introductionmentioning
confidence: 99%